Teaching a history of "race" and anti‐racist action in an academic classroom. Issue 4 (1st March 2019) - Hinton, Mark; Ono‐George, Meleisa
Abstract : In this paper, we critically reflect on the challenges and successes in designing and co‐teaching an interdisciplinary module on the history of "race" and racism and its legacies within British communities today. We do so by returning to the two key questions that shaped the intended learning outcomes, namely: How can we employ an anti‐racist pedagogy within a university classroom that challenges teachers and students to reflect on "race" in their lives and within their communities? Is it possible for the history of "race" and racism to be taught in a way that is academically rigorous and transformative for the students and teachers? Through sharing how the authors addressed these questions, the paper contributes to longstanding, and more recent, efforts within the social sciences and humanities to address racism through learning, teaching and activism. Abstract : In this paper, Mark Hinton and Meleisa Ono‐George reflect on the challenges and successes in co‐teaching an interdisciplinary module on the history of "race" and racism and its legacies within British communities today.